FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN MINYAK BERULANG PADA PELAKU USAHA MAKANAN - Putri Ronitawati; Viki Riantama; Khairizka Citra Palupir (JURNAL RISET GIZI, 2020)
Background: Based on SUSENAS (2013) data for 2013 cooking oil consumption figures were 8,92 liters/capita/year. The prediction of palm cooking oil consumption at the household level in 2014 is 9,21 liters/capita/year. The behavior of using it in the community which has a tendency to be spent by using it repeatedly or leaving oil that is not suitable for disposal into waterways or yards, can have a negative impact on health and the environment because repeatedly used oil can potentially cause cancer and narrowing of blood vessels that can trigger coronary heart disease, stroke and hypertension.Objectives: Knowing the factors related to recurrent oil use in food businesses in DKI Jakarta.Method: This study was conducted in five urban areas in DKI Jakarta by cross-sectional method. The population in this study were all food businesses in DKI Jakarta that use cooking oil, with a total sample of 88 respondents. The analysis used the chi-square test.Results: The results of this study indicate an understanding variable of 0,123, a reason variable of 0,104, a knowledge variable of 0,04, a consideration variable of 0,063, an attitude variable of 0,039, an availability variable of 0,264, and environmental variable of 0,045.Conclusion: These results stated that there was a relationship between knowledge, attitudes, and environment with the behavior of recurrent oil use in food businesses in DKI Jakarta. The next researchers expected to educate food businesses about the correct and appropriate use of recurrent oil.